Construction of Spirolactams by Unexpected Oxidative Cyclization of Alkenyl Diynes via Copper Catalysis - Shi, Chong-Yang; Han, Tao; Hong, Feng-Lin; Ye, Long-Wu; Sun, Qing; Teng, Ming-Yu (Organic letters, 2023)
A copper-catalyzed oxidative cyclization of alkenyl N-propargyl ynamides is described. This protocol enables the practical synthesis of diverse spirocyclic γ-lactams bearing an exocyclic double bond with generally high Z/E selectivity in moderate to good yields. Importantly, this copper-catalyzed oxidative cyclization demonstrates a distinctive selectivity in comparison with the related gold catalysis.